AN ANALYSIS OF STUDENTS' ANXIETY IN SPEAKING ENGLISH AT SMA NEGERI 3 MAKASSAR - Riqah Fahranah; Nurdin Noni; Kisman Salija (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2024)
This research was conducted to determine the level of student anxiety in speaking English, the factors that cause student anxiety in speaking English, as well as strategies for overcoming student anxiety in speaking English. This research uses a mixed methods research type. Students of SMA Negeri 3 Makassar were chosen as research subjects. Data were collected through the FLCAS survey by Horwitz (1986) and semi-structured interviews. From the findings that will occur it can be concluded that (1) The researcher found that the average level of student anxiety in English was at a moderate anxiety level with a percentage of 42% (2) then the researcher also found that several factors of student anxiety were influenced by Communicative Anxiety, test anxiety and Fear of Negative Evaluation. (3) students' strategies for overcoming their anxiety in speaking English are Preparation, Relaxation, and Positive Thinking.